2009
DOI: 10.1371/journal.pone.0004222
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV Infection and Kaposi Sarcoma on Human Herpesvirus-8 Mucosal Replication and Dissemination in Uganda

Abstract: IntroductionKaposi sarcoma (KS) is the leading cause of cancer in Uganda and occurs in people with and without HIV. Human herpesvirus-8 (HHV-8) replication is important both in transmission of HHV-8 and progression to KS. We characterized the sites and frequency of HHV-8 detection in Ugandans with and without HIV and KS.MethodsParticipants were enrolled into one of four groups on the basis of HIV and KS status (HIV negative/KS negative, HIV positive/KS negative, HIV negative/KS positive, and HIV positive/KS po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 40 publications
(54 reference statements)
6
68
0
Order By: Relevance
“…Western and African countries also reported high frequencies of KS among HIV-infected individuals [20,21]. However, the incidence of KS is very low in our region.…”
Section: Tablementioning
confidence: 51%
“…Western and African countries also reported high frequencies of KS among HIV-infected individuals [20,21]. However, the incidence of KS is very low in our region.…”
Section: Tablementioning
confidence: 51%
“…As previously described [10], pregnant women in Kampala were enrolled, and oral swabs were collected in a standardized manner [11] from the mother and all children for quantitative polymerase chain reaction (qPCR) analysis of CMV [12]. Blood samples were collected from the infants at 6 weeks of age and every 4 months thereafter.…”
mentioning
confidence: 99%
“…Kaposi sarcoma is more common in homosexual than heterosexual persons with AIDS. 15 The high prevalence in prepubertal children in endemic areas suggests that sexual transmission is unlikely to be the sole mode of infection. A study of HHV-8 -seropositive men who had sex with men and no clinical evidence of KS showed that exposure to infectious saliva is a risk factor for HHV-8 acquisition.…”
Section: Hhv-8 and Its Epidemiologic Featuresmentioning
confidence: 99%